Hubungan Atensi Belajar Mahasiswa dengan Kondisi Lingkungan Kampus dan Interaksi Edukatif - Yulyeta Paulina Amelia Runtuwene (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2007)
This study is intended to examine the relationship between the two variables of campus environment and classroom interaction and learning attention. Seventy college students were randomly selected, and questionnaires were distributed to them. Correlational analyses as well as bivariate and multiple regression reveal that the level of learning attention improved as the quality of environment and interaction improved. Environment, classroom interaction, or both these two variables contribute significantly to learning attention by 22.1%, 18.9%, and 29.4% respectively.